DESIGN OF THE DOLPHIN TYPE LIQUID BULK PIER STRUCTURE AT THE KOTABARU FUEL OIL TERMINAL, SOUTH KALIMANTAN - Ferdiansyah Batubara, Yusuf
Indonesia is an archipelagic country, with a majority of its territory consisting of seas. This condition makes sea transportation crucial in the lives of Indonesians, especially in the distribution of essential commodities, such as Petroleum (BBM). To enhance effectiveness and efficiency in distributing BBM to the South Kalimantan region, a liquid bulk jetty was constructed at the Oil Fuel Terminal (TBBM) in Kotabaru, South Kalimantan Province. The study location for the design of this jetty is at the Oil Fuel Terminal (TBBM) Kota Baru, Kotabaru Regency, South Kalimantan Province, Indonesia, at coordinates 3°15'11.66"S and 116°12'2.87"E. The jetty is designed to accommodate Triaksa 15 (1524 DWT) and Griya Enim (13960 DWT) vessels. This Final Project discusses the design of a liquid bulk jetty structure, consisting of a loading platform, breasting dolphin, mooring dolphin, trestle, and catwalk. The jetty structure is designed according to the environmental conditions at the jetty location and the loading on the jetty structure, including berthing load, mooring load, dead load, human load, operational load, and environmental load. The preliminary design results in the dimensions of the jetty and the structural elements based on the dominant loading on the jetty. The jetty structure is then modeled using structural analysis software, and optimization or changes to the jetty structure are made until values of UCR (Ultimate Compression Resistance) and deflection meet the design criteria. The output from the structural modeling, after obtaining the optimum design, includes forces in the concrete elements and reaction forces from the jetty structure. These forces are used in the next stage, which is the design of the reinforcement for the structural elements of the jetty. Subsequently, calculations are made for the required pile depth for each structure based on the reaction forces obtained from the structural model and the soil conditions at the jetty location. This Final Project will result in a design plan comprising the dimensions of the jetty and its structural elements, the reinforcement of the jetty's structural elements, and the depth of the jetty's pile.